Gastric Carcinoma and Role of Proximal Gastrectomy - Shahid Hussain Mirani, Munawer Latif Memon, Muhammad Afzal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Comparative analysis of different surgical methods for the treatment of gastric carcinoma with proximal gastrectomy. Study Design: Retrospective study Place and Duration of Study: Department of Surgery Unit-2, Ghulam Muhammad Mahar Medical College, Teaching Hospital, Sukkur, Department of Surgery, Wah Medical College POF Hospital, Wah Cantt and from Department of Surgery, CMH Kharian Medical College, Kharian from 1st January 2015 to 30th June 2021. Methodology: One hundred patients were retrospectively evaluated for the proximal gastrectomy with the previously conducted procedures of open gastrectomy as well as laparoscopic gastrectomy. The patients were compared for the various types of gastrectomy used with the new established proximal gastrectomy method. The patient distribution was based on available resources and patients’ consent. Patients were identified as into two groups where group 1 patients were placed for open total gastrectomy whereas group 2 patients were defined as laparoscopic proximal gastrectomy. All the patients were compared in terms of operation time, recurrence rate and associated complications. Results: Mean age of the study participants were 54.5±3.3 years. Higher frequency of males participants were observed as compared to the females. Estimated blood loss was considerably different in both study groups. Excess blood loss was seen in total gastrectomy in contrast to laparoscopic procedure. Less complication was observed in open gastrectomy than to laparoscopic proximal gastrectomy. Conclusion: Minimally invasive surgical method could be the standard surgical procedure for gastric oncology treatment in which function of the stomach can be preserved along with safety profiles. Therefore, LPG can be a preferable treatment option for other available treatment options. Keywords: Invasive, Oncology, Laparoscopic, Complications, Gastric